Educating Toward Full Inclusion in the Body of Christ: People with Disabilities Being Full Members of the Church - Webb-Mitchell, Brett (Journal of religion, disability & health, 2010)
The focus of this article is on moving beyond the first step or stage of welcoming people with disabilities into congregations in general—particularly through segregated programs and activities or “mainstreaming approaches” for people with intellectual disabilities—toward the full inclusion of people with disabilities into the rich, active life of a church.